C-Terminal Helical Domains of Dengue Virus Type 4 E Protein Affect the Expression/Stability of prM Protein and Conformation of prM and E Proteins - Tsai, Wen-Yang (Public Library of Science, 2012)
BACKGROUND: The envelope (E) protein of dengue virus (DENV) is the major immunogen for dengue vaccine development. At the C-terminus are two α-helices (EH1 and EH2) and two transmembrane domains (ET1 and ET2). After synthesis, E protein forms a heterodimer with the precursor membrane (prM) protein, which has been shown as a chaperone for E protein and could prevent premature fusion of E protein during maturation. Recent reports of enhancement of DENV infectivity by anti-prM monoclonal antibodies (mAbs) suggest the presence of prM protein in dengue vaccine is potentially harmful. A better understanding of prM-E interaction and its effect on recognition of E and prM proteins by different antibodies would provide important information for future design of safe and effective subunit dengue vaccines. METHODOLOGY/PRINCIPAL FINDINGS: In this study, we examined a series of C-terminal truncation constructs of DENV4 prME, E and prM. In the absence of E protein, prM protein expressed poorly. In the presence of E protein, the expression of prM protein increased in a dose-dependent manner. Radioimmunoprecipitation, sucrose gradient sedimentation and pulse-chase experiments revealed ET1 and EH2 were involved in prM-E interaction and EH2 in maintaining the stability of prM protein. Dot blot assay revealed E protein affected the recognition of prM protein by an anti-prM mAb; truncation of EH2 or EH1 affected the recognition of E protein by several anti-E mAbs, which was further verified by capture ELISA. The E protein ectodomain alone can be recognized well by all anti-E mAbs tested. CONCLUSIONS/SIGNIFICANCE: A C-terminal domain (EH2) of DENV E protein can affect the expression and stability of its chaperone prM protein. These findings not only add to our understanding of the interaction between prM and E proteins, but also suggest the ectodomain of E protein alone could be a potential subunit immunogen without inducing anti-prM response.